Interactions with E-Government, New Digital Media, and Traditional Channel Choices: Citizen-Initiated Factors. Issue 3 (19th August 2014) - Reddick, Christopher; Anthopoulos, Leonidas
Abstract : Purpose: Although more than two decades have passed since the initiation of e-government, digital channel choice is still being questioned, compared to traditional channels, and the level of selection with channels is being investigated. This paper examines the factors that can predict citizen-initiated contact with e-government as an attempt to identify important differences between service channel selections. Design/methodology/approach: This study states three research questions that are answered through a literature review and statistical analysis of a survey in a developed country. More specifically, it identifies the factors that impact channel choice and validates them with survey results. To this end, this paper utilizes data from a national Canadian survey, where citizens empirically evaluated their channel choice – e-government, new digital media, and traditional service channels- for government contacts. Findings: Statistical analysis over this data return valuable findings such as that the e-government channel is more appropriate for information collection, while traditional service channels are more likely to establish individual problem solving. Moreover, the digital divide appears to have an impact on citizen channel choice. Furthermore, digitally literate citizens who are aware of privacy issues are more likely to use new digital media. Finally, citizens are quite satisfied from their new digital media experience, but are not as satisfied with their traditional contact experience. Originality/value: These outcomes show that e-government obstacles regarding digital divide, trust and efficiency remain active and have to be addressed more carefully by governments. This study shows that e-government and new digital media are not simple channel choices, but are complex in public service delivery. These outcomes confirm the significance of channel choice for transforming government, since e-government appears to be a part of a broader channel choice agenda.